DE LA TRADUCTOLOGIE DES ÉTATS D’ÂME ET «VICE VERSA»: VERS UNE ÉTUDE DES ASPECTS PSYCHOLOGIQUES EN TRADUCTION - Froeliger, Nicolas (Vertimo studijos, 2017)
Written in French, this paper is a reflection on how to set up a sociological study of translator behavior and decision-making based on the study of actually translated texts. A few hurdles have to be overcome in that perspective: (1) that of insignificance: this research (in the author’s humble opinion) has to be insightful not only for translation studies specialists, but first and foremost to translators themselves; (2) that of striking a balance between outliers (i.e. genuine but isolated cases) and generic (i.e. generalizable, but not meaningful) cases in the context of growing use of computer assisted tools; (3) that of using psychology and sociology in order to build a translation theory rather than the reverse. Eventually, it points toward three instances of acceptability: that of individual and collective behavior, that of the results achieved, and that of the translation professions in the eyes of society at large. The methodological issues raised by such research will be dealt with in a further paper.